Electrical impedance spectroscopy for non-destructive meat freshness assessment - Wang, Shiqian; Zhang, Ziye; Zhao, Xinyao; Xiao, Xinqing (Discover Food, 2024)
The quality of meat is inherently linked to the time of its departure from the processing facility, the conditions of transportation, and the methods of storage, all of which directly affect the meat's integrity. Rapid, non-destructive, and precise evaluation of meat quality has thus emerged as a significant area of interest in recent years. Electrical impedance spectroscopy (EIS), recognized for its high reproducibility, user-friendly nature, non-polluting properties, measurement stability, and controllable error rates, stands out as a cutting-edge, non-destructive technique for quality assessment in today's landscape of equipment, applications, and data analysis methodologies. This paper provides a comprehensive review of the utilization of EIS-based non-destructive sensors for gauging the internal quality of meat, detailing the modalities of measurement and predictive modeling techniques. A critical discourse on the merits and demerits of various biosensors is presented, alongside an examination of the practical applicability of the EIS measurement approach. The paper encapsulates the commonly employed methods for the selection and processing of electrical impedance sensor data, including preprocessing, feature selection, calibration, and validation. Ultimately, the paper posits that the evolution from costly electrochemical devices traditionally used for impedance data collection to more economical, impedance-based devices for estimating meat freshness represents an avenue ripe for future exploration.